Structure‐Tailored Surface Oxide on Cu–Ga Intermetallics Enhances CO2 Reduction Selectivity to Methanol at Ultralow Potential. Issue 19 (7th April 2022) - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C.
Abstract: Electrochemical CO2 reduction reaction (eCO2 RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9 Ga4 ). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of −0.3 V vs RHE. The high performance of CuGa2 compared to Cu9 Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2 O3 ) even in the reduction atmosphere. The Ga2 O3 species is mapped by X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO2 RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2 O3, which is probed by in situ XAFS, quasi in situ powder X‐ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope‐labeling experiments in presence of 13 CO2 . Finally, to minimize the mass transport limitations and improve the overall eCO2 RR performance, a poly(tetrafluoroethylene)‐based gas diffusion electrode is used in the flow cell configuration. Abstract : Cu–Ga‐based intermetallics exhibit extremely high Faradaic efficiency toward methanol (78%) in an electrochemical CO2 reduction reaction. The operando generates gallium oxide, identified as the active material, mapped via potential‐dependent in situ X‐ray absorption, in situ infrared, and ex situ X‐ray photoelectron spectroscopic techniques. The best catalyst shows long‐term stability with high current density in a gas diffusion electrode based flow cell.